A Non-Repudiated and Intelligent RFID Medication Safety Management System. Issue 3 (2nd July 2016) - Chen, Chin-Ling; Lai, Yeong-Lin; Chen, Chih-Cheng; Zheng, Chun-Yi; Chang, Li-Chih
Abstract: Radio frequency identification (RFID) technology is a significant solution for homeland and cyber defense. Patient and cyber safety issues have been regarded as the most important quality policy of hospital management. Enhancing patients' safety and reducing medication errors are priority issues of the World Health Organization (WHO). With the increasing number of inpatients, medication safety is a major concern for doctors, pharmacists, and nurses. In this paper, we employ the RFID, digital certificate, and digital signature to enhance inpatient medication safety management. The proposed scheme can promptly present the information on the inpatient medication and improve the management of the inpatient medication safety. It not only enhances the quality of medical treatment but also provides non-repudiated and intelligent medication safety management. In our scheme, the automated medication dispensing machine (AMDM) is equipped with RFID tags and readers to improve the medication safety. The comprehensive analysis of the key performance indicator (KPI) of our scheme shows a significant 50% reduction in total cost and increased satisfaction on the part of hospital nurses.